Varicella in a dental practice – report of two cases of the disease with oral involvement - Ślebioda, Zuzanna; Dorocka-Bobkowska, Barbara (Journal of Stomatology, 2019)
Varicella-zoster virus (VZV) infection is common in children and adolescents and in most cases it is an acute but self-limiting condition. The majority of episodes presents with a pruritic, vesicular rash, which develops after 10- to 21-day incubation period. The initial, general symptoms usually include fever, malaise, headache and abdominal pain. However, rarely, serious complications, including pneumonia, cerebral ataxia or pyoderma, may develop as a consequence of this infection. Primary infection results in a lifetime latency of the virus in nerve ganglia and may lead to the development of zoster (shingles) in future. This paper presents two cases of familial transmission of varicella that involved the oral cavity. Both oral and genital mucosa were affected. The oral findings included vesicles, which shortly transformed into erosions, and the exacerbation of geographic tongue, which was observed simultaneously with the development of a general infection. In the paper we describe the sequence of the development of mucocutaneous lesions and we discuss the options of systemic and local treatment in the oral cavity. We show the role of a dentist in the diagnostic process and during the recovery period of a patient infected with varicella and we discuss the methods of prophylaxis.